Fertilization of Ascidians: Gamete Interaction, Self/Nonself Recognition and Sperm Penetration of Egg Coat - Saito, Takako; Sawada, Hitoshi (Frontiers in Cell and Developmental Biology, 2022)
Fertilization is one of the most important events in living organisms to generate a new life with a mixed genetic background. To achieve successful fertilization, sperm and eggs must undergo complex processes in a sequential order. Fertilization of marine invertebrate Ciona intestinalis type A has been studied for more than a hundred years. Ascidian sperm are attracted by chemoattractants from eggs and bind to the vitelline coat. Subsequently, sperm penetrate through the vitelline coat proteolytically and finally fuse with the egg plasma membrane. Here, we summarize the fertilization mechanisms of ascidians, particularly from sperm-egg interactions to sperm penetration of the egg coat. Since ascidians, including C. intestinalis, are hermaphrodites, inbreeding depression is a serious problem. To avoid self-fertilization, ascidians possess a self-incompatibility system. In this review, we also describe the molecular mechanisms of the self-incompatibility system in C. intestinalis governed by three allelic gene pairs of s-Themis and v-Themis.